Luminescence Sensitivity of Quartz From Rocks Under in situ Chemical Weathering Conditions - Cao, Zheng; Jiang, Yingying; Xu, Jiandong; Zhao, Juxing; Zhao, Cheng (Frontiers in Earth Science, 2022)
In provenance investigation of Quaternary sediments, quartz luminescence sensitivity (QLS) has been employed as a technique. The weathering and influence on the earliest signs of luminescence sensitivity of sedimentary quartz require more consideration. In this study, the QLS properties of eight samples of Permian biotite monzogranite from a borehole in the southern tropics of China are investigated. The degree of chemical weathering does not correspond with the QLS values of samples that have undergone varying degrees of in situ weathering. We hypothesize that the variation of the irradiation field during the in situ chemical weathering process may affect the QLS, but not considerably within 200 ka. In addition, we discovered that quartz from the same source undergoes varying degrees of in situ chemical weathering, but has a constant response to irradiation-bleaching cycles (IBCs). The presence of variances in the thermal activation curves (TACs) of the same rock body indicates that further research is required to apply TAC as a provenance indicator.